A Study of Comprehensibility of Javanese as Used by Master of Ceremony (Pranatacara) - ., Sukarno (KnE Social Sciences, 2018)
The current study is aimed at examining the level of comprehensibility of Javanese as used by a pranatacara with a particular emphasis on the young generation of Javanese. In one wedding reception, 50 people, aged ( judging from their appearance) between 20 and 35 years old, were interviewed on how much they understood the Javanese spoken by the master of ceremony (pranatacara). The criteria for assessment were set as: (1) fully understood, (2) partly understood, and (3) did not understand. The findings indicate that most of the subjects (74%) partly understood, 10% fully understood, and the rest (16%) did not understand. The reasons for comprehensibility varied from one subject to another. As a local language of high cultural heritage, Javanese has to be preserved in all its manifestations. As a preliminary research, this does not fully describe the real situation. Other studies must be conducted, employing different methods, subjects, and settings. However, it is important that special steps be undertaken to preserve Javanese as a local language of high cultural heritage. Keywords: comprehensibility, cultural heritage, Javanese, pranatacara